Analysis of Environmental Education (PLH) Content in Junior High School Science Textbooks - Siti Rukoyah; Suroso Mukti Leksono; Lukman Nulhakim (CV. Rayyan Dwi Bharata, 2023)
Environmental problems are caused by natural and human factors, but human activities have a greater influence on the environment, one of which causes pollution. Efforts to include environmental education in formal education are one solution to overcome environmental problems through textbooks. The purpose of this study is to analyze the content of environmental education content in junior high school science textbooks, which include humans and the environment, maintaining environmental cleanliness, natural resources, water, air, land and land, energy, forests, natural disasters, coastal and sea, rivers and lakes. The method used in this study is descriptive qualitative. The instruments used are documentation sheets and instrument assessment sheets. The data analysis technique of this research uses Miles theory. The results showed that the overall environmental education sub-content has not been well covered in junior high school science textbooks. Sub-content that has not been covered includes the social environment and its role, the physical environment and its changes, the influence of globalization on behavior change, prevention of the influence of globalization, understanding waste, types of waste, maintenance of waterways, the influence of noise and odor on health, understanding landslides, types of landslides, land degradation, forest functions, marine and coastal ecosystems, coastal management, river and lake ecosystems, river and lake benefits, sedimentation and siltation. It can still be developed by integrating environmental education sub-content in junior high school science textbooks.